Impact of CT imaging on predicting the surgical management of acute diverticulitis - Shin, Seonhui (Ann Surg Treat Res, 2018)
PURPOSE: The incidence of colonic diverticular disease is increasing, and several grading systems based on CT findings have been developed. The objective of this study was to define the impact of various CT findings of colonic diverticulitis and to demonstrate which factors affect the need for operative treatment. METHODS: Three hundred fifty-seven patients diagnosed with colonic diverticulitis from January 2010 to July 2016 were retrospectively evaluated. Patients were excluded if pure diverticulosis, diverticular bleeding, colon cancer, or relevant data deficiencies, and the remaining patients (n = 178) were reviewed. Patients were categorized into a successful nonoperation group and an operation group. The operation group was then matched 1:2 with the nonoperative group based on age, gender, American Society of Anesthesiologists physical status classification, and body mass index. RESULTS: After propensity score matching, there were no significant differences regarding patients' demographic characteristics between the 2 groups. Left location was more associated with need for operation than the right side (79.2% vs. 31.3%, P < 0.001). CT findings such as distant intraperitoneal air, pericolic air, and free fluid were significantly more apparent in the operation group. When these factors were evaluated in a multivariate analysis, distant intraperitoneal air showed statistical significance (P = 0.046) and pericolic air and left location a significant trend (P = 0.071 and P = 0.067, respectively). CONCLUSION: This study suggests that distant intraperitoneal air is the most important factor in the need for surgery in patients with colonic diverticulitis. Further study will be able to identify more detailed CT findings and verify their significance, and will be helpful in designing practical scoring and classification systems.